Pressure Transient Behaviour of Horizontal Wells in a Bounded Reservoir with Gas Cap and Aquifer - Sabila, Tsani (IRC, 2015)
Increased productivity can be seen as a result of horizontal well applications in some certain reservoir conditions. Consequently, there exist the need to monitor the performance of the horizontal wells and characterising the reservoir surrounding it. The literature provided limited study on pressure transient behaviour of horizontal wells in a reservoir with vertical constant pressure boundaries and even lesser investigating completely bounded reservoir (in all x, y, z) directions. An analytical solution is thus presented for the pressure transient response of horizontal wells in an anisotropic, rectangular, homogeneous reservoir, bounded by gas cap and aquifer and laterally, by no-flow boundaries. Solutions were formulated using Green’s and source function method in combination with Newman product method. Type curves analysis and detailed discussion of each flow regimes exhibited are thoroughly investigated. Different dimensions of rectangular-shaped reservoirs and the effects of varying distance of the horizontal well to outer boundaries are included in this study. It could be observed that the pressure behaviour and flow regimes exhibited depend on the type of outer boundaries, distance of the well to the nearest boundary and length of horizontal well itself. Common flow regimes usually associated with horizontal wells were masked by the constant pressure behaviour